2015
DOI: 10.1111/ceo.12508
|View full text |Cite
|
Sign up to set email alerts
|

Current landscape of direct‐to‐consumer genetic testing and its role in ophthalmology: a review

Abstract: The sequencing of the human genome has seen the emergence of the direct-to-consumer (DTC) genetictesting market, which allows individuals to obtain information about their genetic profile and its many health and lifestyle implications. Genetics play an important role in the development of many eye diseases, however, little information is available describing the influence of the DTC industry in ophthalmology. In this review, we examined DTC companies providing genetic test products for eye disease. Of all eye … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The scientific authors of two recent reviews of direct-to-consumer genetic testing for age-related macular degeneration concluded that routine testing for future risk of age-related macular degeneration is not warranted currently, in part because of the wide variation in cost and scope for existing clinical genetic tests and in part because of questions of clinical utility. 16 , 17 Authors of a cost-utility analysis found that genetic screening for age-related macular degeneration that would allow for early treatment with ranibizumab therapy for neovascular macular degeneration would be cost effective. 20 To our knowledge, our study is the first of its kind to evaluate response to predictive genetic testing from a patient perspective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scientific authors of two recent reviews of direct-to-consumer genetic testing for age-related macular degeneration concluded that routine testing for future risk of age-related macular degeneration is not warranted currently, in part because of the wide variation in cost and scope for existing clinical genetic tests and in part because of questions of clinical utility. 16 , 17 Authors of a cost-utility analysis found that genetic screening for age-related macular degeneration that would allow for early treatment with ranibizumab therapy for neovascular macular degeneration would be cost effective. 20 To our knowledge, our study is the first of its kind to evaluate response to predictive genetic testing from a patient perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this recommendation from the American Academy of Ophthalmology, a number of tests are available clinically and direct-to-consumer, with highly variable results in estimated lifetime risk of age-related macular degeneration and calls for inclusion of more genetic information and environmental risk factors to improve age-related macular degeneration prediction accuracy. 16 , 17 A pilot study in 49 smokers demonstrated that people given high genetic risk information were more likely to quit smoking than generic or low genetic risk groups. 18 …”
mentioning
confidence: 99%
“…The company that provided the testing described here has since declared bankruptcy in California Central Bankruptcy Court (Company Bankruptcy Information for Existence Genetics, LLC., n.d.). However, new companies are still entering the direct access genomics market, so the risk of similar false positive results remains (Sanfilippo et al 2015;Vrecar et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to such biological insights, it is possible to calculate a genetic risk score for many complex diseases. Currently, however, accredited genetic testing for these types of diseases is not recommended by peak bodies such as the American Academy of Ophthalmology, due to limited clinical validity and utility of such tests . Despite clear evidence that particular common single nucleotide polymorphisms (SNPs) alter risk for disease, the relative risks are small and are typically less predictive of disease state in the individual than traditional clinical measures and lifestyle factors.…”
mentioning
confidence: 99%
“…Despite the clearly premature nature of genetic testing for most complex diseases, direct‐to‐consumer genetic testing is a reality. In this issue, Sanfilippo and colleagues review the current state of direct‐to‐consumer testing, particularly in relation to ophthalmic conditions . They report that the most commonly offered ophthalmic test is for AMD, but that the SNPs tested, the costs and the clarity of the information provided to customers before and after testing vary significantly between companies.…”
mentioning
confidence: 99%